PEMETAAN POTENSI SUMBER DAYA AIR UNTUK PERTANIAN LAHAN PRODUKTIF (STUDI KASUS: DESA KAMBUHAPANG DAN DESA KAMBATAWUNDUT) - Wilis, Kezia Georginia Patricia; Krisnayanti, Denik Sri; Cornelis, Remigildus (JURNAL SUMBER DAYA AIR, 2024)
Desa Kambuhapang and Desa Kambatawundut are villages located in the Lewa District of East Sumba Regency. This area is characterized by arid conditions and experiences an 8-month-long dry season. Most of the population in this region is engaged in agriculture, particularly dryland farming. The main water supply for agriculture in this area comes from low rainfall, resulting in limited water availability. The purpose of this study is to assess the water discharge potential in these two villages. Secondary data, including rainfall data, was obtained from two stations: the Waingapu meteorological station and the Lewa Paku rain station. Additionally, climatological data from 2012 to 2021 was used. ArcGIS 10.7 software was employed to map the area using Digital Elevation Model (DEM) data. The Modified Penman method was used to determine evapotranspiration, while the F.J. Mock method was applied to calculate the reliable discharge. The results showed that the average annual water availability, according to the F.J. Mock method, is 16.45 m³/s for the Lay Mbeda River and 16.54 m³/s for the Wai Wei River. The villages of Kambuhapang and Kambatawundut have sufficient water availability, with a total of 74.18% across an area of 63.12 km². The adequate water availability in these two villages is evident from the minimum discharge during the dry season, ranging from 6.60 to 7.12 m³/s. This indicates that the villages have sufficient water resources to support the expansion of productive agricultural land for the local community. The utilization of these water resources could be further optimized by providing supporting infrastructure to increase runoff storage, such as water reservoirs, small ponds, or retention basins.Keywords: mapping, water potential, water availability, waingapu, lewa paku